CHILD'S NARRATIVE STRUCTURE - Kumala, Sonya Ayu (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2022)
At its daily used in adult individuals and children, language meet the communication function is to communicate ideas (thought) of an individual in others (Piaget, 2005: 1). This can be evident from the speech-speech or narrative generated in the use of everyday language which then becomes an interesting study for the main study in the use of language in children. In narrating the story, just as it had done by adult speakers, children will also make the selection and preparation of experience and other stories from the story of his life (life story). This explains the narrative as a genre that is universal because it narrated traditions can be found in every culture and speakers of different languages ​​(Hatch: 1992 in Brockmeier 1998). On the other hand, the narrative is also characterized as being bound by culture and language so that in the context of language and speakers of different backgrounds will have the tools possible narrative and discursive different linguistic (Labov & Waletsky: 1968, Ochs: 1998 in Berman 1998). The above facts indicate that the narrative structure generated by the speakers of a language and culture will be different from the speakers of the language with cultural and language backgrounds other.